PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL) UNTUK MENINGKATKAN HASIL BELAJAR IPA TERPADU SISWA KELAS VIII MTS MOHAMAD HEKAL TAHUN PELAJARAN 2024/2025 - Deliana; Pitri Handayani; Arista Ratih (Hiradika | Hira Institute, 2025)
This research is motivated by the implementation of science learning for eighth-grade students at MTs Mohamad Hekal, which is still dominated by a conventional, teacher-centered approach. The teacher acts as the sole source of information, while students tend to be passive, simply receiving material without engaging in critical thinking, exploration, or problem-solving. This impacts learning outcomes, which generally do not meet the school's Minimum Completion (KKM) score. This study aims to improve science learning outcomes for eighth-grade students at MTs Mohamad Hekal. The type of research used is Classroom Action Research. The subjects were 28 eighth-grade students at MTs Mohamad Hekal. The research instruments used were observation sheets of teacher and student activities, as well as assessment test questions. The results showed an increase in teacher and student activity. Teacher activity in Cycle I, Meeting 1, was 80%, Meeting 2, 90%, and in Cycle II, Meetings 1 and 2, increased to 100%. The increase in teacher activity from cycle I to cycle 2 was 15%. Student activity in Learning Activity Meeting 1 was 80%, and in Cycle I, Meeting 2 increased to 85%. Then in cycle II, it increased to meeting one by 90% and in meeting 2 to 96%. There was a 10.5% increase in student learning activity. Student learning outcomes, with an average value of 75.18 in Cycle I and 80.26 in Cycle II, showed a 5.08-point increase. From the study's results, it was concluded that the application of the Project-Based Learning Model (PjBL) in science subjects can improve teacher activity, student activity, and learning outcomes for class VIII students at MTs Mohamad Hekal.